(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of this work was to make LDPE /a.PP blends for economically attractive by (10/90, 20:80, 30:70, &50:50 w/w) ratios via injection molding carried out under 180 o C injection temperatures and to evaluate their mechanical properties including :( Density, Tensile Strength, Elongate to Break, Impact Strength, Bending Modulus,& Young’s Modulus . we notice that the blend behavior dependent on its composition, and injection temperature . Results show there are an increasing of impact strength and bending modulus with increasing of (LDPE) contain and the highest value of these properties were at (50:50) weight ratio, while it has the highest Young’s modulus at (30:70) wt%. 180 o C as injection temperature leads to translate the mechanical behavior from ductile to stiff behavior. DSC curves show that the blends is immiscibility , also thermal degradation was decreased with increasing of LDPE to (50%).Also the Melt flow index decreased from (5.04)-(4.01) (g/10 min) with increasing of LDPE from (30%) to (50%).